PERFORMANCE OF THE NURSING TEAM IN THE HUMANIZATION OF NORMAL DELIVERY - Anne Arruda Marques, Mayara; Lucia de Medeiros, Ana (Health and Society, 2021)
Historically, birth was considered a natural event, respected until the sixteenth century as an exclusively female movement. From the moment that the delivery began to happen inside the hospital with the participation of doctors in the process of the same, the woman stopped being the most important person and active of that event. Therefore, in order to change in this scenario, the World Health Organization and the Ministry of Health have been guiding and implementing behaviors that should be stimulated during childbirth, such as the presence of a companion, the supply of fluids, the use of non-invasive techniques for relief of pain and freedom of choice of birth position, among others. The study aims to verify in the literature the systematization of knowledge about the awareness of the benefits of normal delivery, pointing out the behaviors performed that favor the woman's role. This is a literature review, with descriptive and explanatory character, in the databases Scientific Electronic Library (ScIELO), Latin American and Caribbean Literature in Health Sciences (LILACS); And the National Library of Medicine (PUBMED, from 2008 to 2019), using the following descriptors: normal delivery, humanization, humanization in normal birth, women's role, and the result was three categories: The synthesis of the articles allowed us to understand that there are already some changes in the care of women during labor, but that there is still a lack of knowledge about the role of women in the labor market. It is concluded that in order for women to take part in labor and delivery, humanization becomes necessary, which is evidenced by the need to improve access and quality of delivery services.